Dope in sport as research topic (Russian contributions review) - Anikina, A. V.; Anikin, V. I. (The Russian Journal of Physical Education and Sport, 2018)
In 2014, the anti-Russian doping scandal led to the squeezing of Russia from the ranking of world sports powers. Sport became an arena of competition without rules. Materials and methods. The article analyzes the research data published and presented in the Russian scientific electronic library since the start of the doping scandal in 2014 to the present. General theoretical methods and comparison are used. Results. The study of the works subjects revealed their key areas: medical-biological, legal and psychological-pedagogical. It is shown that in medical research a classification of means and methods for increasing physical performance is given, risk factors and consequences of doping are assessed. They are included in the context of post professional health and rehabilitation. It is revealed that publications in the field of law designate a complex of legal problems in connection with the use of pharmaceuticals in sports. It outlines the range of persons who are legally responsible for the use of doping. The need to develop special branches of sports law as well as sports medical law is emphasized. The question of developing anti-doping legislation in the Russian Federation is raised. It is shown that in the psychological and pedagogical works of domestic authors, the undeveloped subjects of the doping use are noted. The necessity of reformatting the system of athletes and coaches special training is considered. The problem of childrens sports and socialization of the younger generation is being actualized in the context of the fight against the use of doping. Conclusion. In the Russian publications the discussed subjects were on the periphery of scientific thought. Therefore, they did not receive a thorough and comprehensive development with a system analysis of current problems. The methods of overcoming the negative situation taking shape in the Russian Federation are adequately reflected. It was another confirmation of the fact that the country was not ready for a massive discrediting of Russian sports by Western media. Keywords: dope, high-level sport, data analysis, medical-biological research, quality of legal research, psychological and pedagogical researches, defamation, reverse the situation.